Inhibiting Mn Migration by Sb‐Pinning Transition Metal Layers in Lithium‐Rich Cathode Material for Stable High‐Capacity Properties. Issue 24 (12th May 2022) - Cao, Fei; Zeng, Weihao; Zhu, Jiawei; Xiao, Jinsheng; Li, Zilan; Li, Ming; Qin, Rui; Wang, Tingting; Chen, Junxin; Yi, Xiaoli; Wang, Jiexi; Mu, Shichun
Abstract: Owing to the interacted anion and cation redox dynamics in Li2 MnO3, the high energy density can be obtained for lithium‐rich manganese‐based layered transition metal (TM) oxide [Li1.2 Ni0.2 Mn0.6 O2, LNMO]. However, irreversible migration of Mn ions and oxygen release during highly de‐lithiation can destroy its layered structure, leading to voltage and capacity decline. Herein, non‐TM antimony (Sb) is pinned to the TM layer of LNMO by a facile sol‐gel method. High‐resolution ex and in situ characterization technologies manifest that the introduction of trace Sb inhibits the migration of Mn ions, forming a more stable structure. Sb can impressively adjust the Mn‐O interaction between anions and cations, beneficial to decrease the energy level of Mn 3d and O 2p orbitals and expand their band gap according to the  theoretical calculation results. As a result, the discharge specific capacity and the energy density for SbLi1.2 [Ni0.2 Mn0.6 ]O2 (SLNMO) reaches as high as 301 mAh g −1 and 1019.6 Wh kg −1 at 0.1 C, respectively. Moreover, the voltage decay is reduced by 419.8 mV compared with LNMO. The regulative interaction between Mn 3d and isolated O 2p bands provides an accurate guidance for solving electrochemical performance deficiencies of lithium‐rich manganese‐based cathode oxide. Abstract : The interaction between Mn 3d and O 2p bands in lithium‐rich manganese‐based layered oxide cathode materials is effectively regulated by Sb‐pinning in transition metal layers, achieving a stable layered structure and excellent electrochemical performance.